Nanocomposite Membranes for Polymer Electrolyte Fuel Cells - Krishnan, Nagappan Nambi; Henkensmeier, Dirk; Jang, Jong Hyun; Kim, Hyoung-Juhn (WILEY-V C H VERLAG GMBH, 2014)
Nanoparticles are known to play several roles as polymer fillers, among them reducing the bulk material price or adjusting the mechanical properties. In ion conducting polymer membranes, nanoparticles are also used to manipulate the water balance and fuel permeability of the membrane and to increase the ion conductivity. Suitable materials are metal oxides (SiO2, TiO2, etc.), electron deficient boron nitride or ion conductive functionalized metal oxides (S-ZrO2, HPA-SiO2, etc.). This article shows which membrane properties can be addressed by adding nanoparticles and describes the underlying mechanisms.